2008
DOI: 10.1529/biophysj.108.133736
|View full text |Cite
|
Sign up to set email alerts
|

The Bound States of Amphipathic Drugs in Lipid Bilayers: Study of Curcumin

Abstract: Drug-membrane interactions are well known but poorly understood. Here we describe dual measurements of membrane thickness change and membrane area change due to the binding of the amphipathic drug curcumin. The combined results allowed us to analyze the binding states of a drug to lipid bilayers, one on the water-membrane interface and another in the hydrocarbon region of the bilayer. The transition between the two states is strongly affected by the elastic energy of membrane thinning (or, equivalently, area s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 27 publications
13
100
1
3
Order By: Relevance
“…These results were in agreement with Zhongfa et al who reported that PEG400 was capable of solubilizing curcumin to a higher extent (Zhongfa et al, 2012). W.W. Quitschke (2012) explained the solubilization power of PEG by its amphiphilic properties confirming Mandeville et al (2009) andSun et al (2008) observations that curcumin requires hydrophobic and hydrophilic moieties balance, in addition they described the solubility behavior of curcumin as amphipathic.…”
Section: Solubility Studysupporting
confidence: 91%
“…These results were in agreement with Zhongfa et al who reported that PEG400 was capable of solubilizing curcumin to a higher extent (Zhongfa et al, 2012). W.W. Quitschke (2012) explained the solubilization power of PEG by its amphiphilic properties confirming Mandeville et al (2009) andSun et al (2008) observations that curcumin requires hydrophobic and hydrophilic moieties balance, in addition they described the solubility behavior of curcumin as amphipathic.…”
Section: Solubility Studysupporting
confidence: 91%
“…The results support the hypothesis that curcumin penetrates the inner layer of the membrane when present at relatively high concentrations [16][17][18]. Furthermore, because electrochemical techniques can monitor the behavior of curcumin directly, they allow convenient assessment of how the dynamic parameters (such as curcumin concentration) influence the curcumin/substrate interaction.…”
Section: 1supporting
confidence: 78%
“…Their results revealed that curcumin increases both gramicidin channel lifetimes and appearance rates, suggesting that curcumin decreases the energetic costs of the bilayer deformations. Further work by Huang et al [16,17] has shown that curcumin can bind to the membrane in two modes: a surface-associated mode at low curcumin concentrations and a transmembrane mode at high concentrations. Furthermore, Barry et al [18] have studied the physical changes of membrane induced by curcumin using a combination of solid-state NMR and differential scanning calorimetry (DSC).…”
mentioning
confidence: 99%
“…Second, the relatively high partition coefficient of curcumin is indicative of the molecule's capacity to interact with biomembranes (Jaruga et al, 1998), which is reflected by the intercalation of curcumin into model membranes (liposomes) composed of saturated (dipalmitoylphosphatidyl choline or dimyristoylphosphatidyl choline) (Barry et al, 2009;Perez-Lara et al, 2010), monounsaturated (dioleoylphosphatidyl choline) (Ingolfsson et al, 2007;Hung et al, 2008;Sun et al, 2008), or egg yolk phosphatidyl cholines (Kunwar et al, 2006;Karewicz et al, 2011). The association of curcumin with model membranes occurs at relatively high partition constants, i.e., in the range of 2.5 Â 10 4 M 21 (Kunwar et al, 2006) to 4.3 Â 10 4 M 21 (Karewicz et al, 2011) for egg yolk phosphatidylcholine liposomes and 2.4 Â 10 4 M 21 for dioleoylphosphatidyl choline liposomes , indicating that curcumin can be taken up by cells by direct intercalation into the cell membrane.…”
Section: H-bond Accepting Capacity Of the Methoxy Groupsmentioning
confidence: 99%